Improve Security of Cloud Storage by Using Third Parity Authentication, One Time Password and Modified AES Encryption Algorithm - Firas A. Abdulatif; Maan Zuhiar (Institute of Advanced Engineering and Science, 2018)
Cloud computing is a new term to provide application and hardware as service over the internet. Demand for cloud has increased dramatically in recent years. However, a major drawback for cloud adoption is lack of security so that we will try to solve some security issues related to cloud storage by design and implement a secure system to store privet data in cloud storage. This secure system provide secure login to cloud by using third parity authentication (smart phone) and one time password depend on chaotic system to prevent unauthorized people from get access to cloud and modified AES algorithms to encrypt the data in the cloud storage.